2013
DOI: 10.1093/molbev/mst104
|View full text |Cite
|
Sign up to set email alerts
|

The Evolutionary History of Plasmodium vivax as Inferred from Mitochondrial Genomes: Parasite Genetic Diversity in the Americas

Abstract: Plasmodium vivax is the most prevalent human malaria parasite in the Americas. Previous studies have contrasted the genetic diversity of parasite populations in the Americas with those in Asia and Oceania, concluding that New World populations exhibit low genetic diversity consistent with a recent introduction. Here we used an expanded sample of complete mitochondrial genome sequences to investigate the diversity of P. vivax in the Americas as well as in other continental populations. We show that the diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

22
108
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(136 citation statements)
references
References 56 publications
(110 reference statements)
22
108
3
3
Order By: Relevance
“…[34][35][36] A very recent analysis of mitochondrial lineages of P. vivax sampled across the Americas confirmed the high level of genetic diversity and substructuring of local parasite populations, with at least four well-defined haplotype clusters. 37 These data are consistent with the introduction of P. vivax in the Americas from multiple sources and at different times since the first humans reached the continent in preColumbian times. This hypothetical scenario may explain why some mitochondrial lineages of American parasites cluster together with the lineages from Africa and south Asia and a few lineages are connected to Melanesian lineages, whereas most lineages have clearly diverged from all other P. vivax populations (Figures 1 and 2).…”
supporting
confidence: 79%
“…[34][35][36] A very recent analysis of mitochondrial lineages of P. vivax sampled across the Americas confirmed the high level of genetic diversity and substructuring of local parasite populations, with at least four well-defined haplotype clusters. 37 These data are consistent with the introduction of P. vivax in the Americas from multiple sources and at different times since the first humans reached the continent in preColumbian times. This hypothetical scenario may explain why some mitochondrial lineages of American parasites cluster together with the lineages from Africa and south Asia and a few lineages are connected to Melanesian lineages, whereas most lineages have clearly diverged from all other P. vivax populations (Figures 1 and 2).…”
supporting
confidence: 79%
“…Previous analyses suggested an Asian origin based on high mtDNA diversity in this region, but are likely to have been influenced by the lack of African parasites in the sample and by demographic processes such as population expansion, which increases diversity. 44 There have been some attempts to understand how P. vivax subsequently spread around the world using mtDNA [34][35][36]45 ; however, the population structure is complex and requires further deep sampling of strains from all major endemic regions. Nevertheless, some important insights have been gained into the evolutionary history of P. vivax in different geographic regions.…”
Section: Emergence Global Spread and Evolutionary Historymentioning
confidence: 99%
“…Nevertheless, some important insights have been gained into the evolutionary history of P. vivax in different geographic regions. For example, in South America, there is low local diversity but high divergence consistent with multiple independent introductions 35 possibly from a European source with origins in Africa. 45 Whereas in the Asia Pacific, high local diversity is observed, consistent with ancient population expansion and complex migration patterns.…”
Section: Emergence Global Spread and Evolutionary Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, it has been suggested that modern African parasites, at least in the Horn of Africa and Madagascar, could have been reintroduced via the import of East Asian/Indian P. vivax to the coastal areas of East Africa by early seagoing traders and that this could explain their lack of diversity (4). Intriguingly, the diversity of the American strains is comparable to those found in Oceania and Asia (8), raising questions regarding the origin of these strains. Some of the American strains are thought to have been brought there from Europe by Spanish sailors and colonists in the last few centuries (4,9).…”
mentioning
confidence: 99%